Anthropometric and performance differences among high-school football players - Dupler, T. L.; Amonette, W.E.; Coleman, A. E.; Hoffman, J. R; Wenzel, T. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to examine physical and performance differences between grade levels and playing positions within High-School football players. Two thousand three hundred and twenty-seven athletes were tested for height, weight, 40-yd sprint time, proagility time, and vertical jump height. Mean scores across age groups and playing positions were compared using repeated-measures analysis of variance (ANOVA) and 1-way ANOVAs. The results indicate that defensive players in the 11th and 12th grades were significantly faster in the 40-yd sprint, quicker in the proagility, and generated more power than 9th and 10th grade defensive players across all positions (p < 0.05). Similarly, offensive players in the 11th and 12th grades were significantly faster, quicker, and jumped higher than did football players in lower grades (p < 0.05). Overall, these data suggest that there are distinct differences in the physical and performance characteristics of high-school football players. The greatest difference is observed between the sophomore and junior years. Older, more mature athletes are faster, quicker, and capable of generating more power than younger athletes. Practically, these data lend support to the common 3-tiered approach (i.e., Freshman, Junior Varsity, and Varsity) most high schools use for their football programs. This approach is likely indicated to allow for physical maturation of young players and to allow time for the development of strength, power, speed, and agility necessary to compete with older players.